Cultural accommodation of internet-based interventions for substance use and related disorders: a proposed comprehensive framework based on a pilot study and a literature review - Gueta, Keren; Harel-Fisch, Yossi; Walsh, Sophie D. (Frontiers in Psychology, 2023)
Despite the low utilization rates of substance use and related disorders services, and the ability of internet-based interventions for substance use and related disorders (IBIS) to address challenges related to service engagement, limited attention has been placed on the processes for the accommodation of these interventions to diverse cultural settings. This study aimed to develop a framework for the cultural accommodation of IBIS across populations based on a pilot study and a literature review. A pilot study of cultural accommodation of an existing internet intervention for alcohol use was carried out in Israel, which involved focus groups and daily online surveys of prospective consumers (N=24) as well as interviews with experts (N=7) in the substance abuse treatment field. Thematic analysis revealed a range of themes that relate to the general Israeli culture and the specific Israeli drinking subculture, identified as needing to be addressed in the process of intervention accommodation. A comprehensive framework for cultural accommodation of IBIS is suggested, consisting of five stages: Technical and cultural feasibility; Engagement of target group; Identification of accommodation variables, Accommodation, and evaluation of the accommodated intervention. In addition, the framework consists of four dimensions of accommodation: Barriers and facilitators; Audio-visual materials and language; Mechanisms of change; Intersectional factors. We suggest that the proposed framework may serve as a guide for the cultural accommodation of existing internet-based interventions for substance use and related disorders across a range of cultural and geographical settings, thus augmenting the ecological validity of internet-based interventions for substance use and related disorders, expanding cross-cultural intervention research, and reducing health disparities worldwide.